Proceedings of the 2007 SIAM International Conference on Data Mining 2007
DOI: 10.1137/1.9781611972771.42
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Time-Changing Data with Adaptive Windowing

Abstract: We present a new approach for dealing with distribution change and concept drift when learning from data sequences that may vary with time. We use sliding windows whose size, instead of being fixed a priori, is recomputed online according to the rate of change observed from the data in the window itself. This delivers the user or programmer from having to guess a time-scale for change. Contrary to many related works, we provide rigorous guarantees of performance, as bounds on the rates of false positives and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
893
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,195 publications
(915 citation statements)
references
References 16 publications
0
893
0
22
Order By: Relevance
“…In [14] learning from concept-drifting data streams is performed based on a sliding window of an adaptive size. The window size increases when no change is apparent and it shrinks when data changes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14] learning from concept-drifting data streams is performed based on a sliding window of an adaptive size. The window size increases when no change is apparent and it shrinks when data changes.…”
Section: Related Workmentioning
confidence: 99%
“…By assigning weights to ensemble members depending on the estimated error rate, concept drift can be dealt with [15]. In [16], two ensemble methods, bagging by ADWIN (ADaptive WINdowing) [14] and bagging by adaptive-size Hoeffding trees, are proposed.…”
Section: Related Workmentioning
confidence: 99%
“…A method to adapt to concept drifts in the data stream is to use a sliding window that only contains most recent data samples [13] [14]. The use of a sliding window also has the advantage of limiting both the computational cost and the memory requirement.…”
Section: Online Classification and Evolving Systemsmentioning
confidence: 99%
“…However, in case of an increasing error rate that reaches the second threshold, a concept change is declared and the learning model is retrained from the buffered data that appeared after t w . [2,3] proposed an adaptive sliding window scheme named ADWIN for change detection and for estimating statistics from the data stream. It was shown that the ADWIN algorithm outperforms the SPC approach and that it has the ability to provide rigorous guarantees on false positive and false negative rates.…”
Section: Statistical Process Control (Spc)mentioning
confidence: 99%